Typification of the names associated with Anogramma lorentzii (Pteridaceae: Pteridoideae) - Arana, Marcelo D.; Oggero, Antonia J.; Angeli, Juan P. (Phytotaxa, 2016)
The genus Anogramma Link (1841: 137) comprises about six species of tropical and temperate regions of America, Ascension Island, southern Europe and Africa east to New Zealand (Tryon & Tryon 1982). The genus is distinguished especially by the annual habit of the sporophyte and the persistence of the gametophyte by means of tubercles.